Realnost in mitičnost zelenega Pohorja: literarno-likovni monolit Jožeta Tomažiča in Jožeta Beráneka - Haramija, Dragica; Duh, Matjaž (Revija za elementarno izobraževanje, 2008)
The Reality and Mythicism of Green Pohorje: The Literary and Artistic Monolith of Jože Tomažič and Jože Beránek. Jože Tomažič (1906-1970) gained his importance especially as a writer of youth prose, although he spent the last years of his life focusing on stage-related activities. His books were issued during the Second World War and by publishing, he violated the cultural silence of that time. That seemed to be the reason why he was overlooked in the after war period. Since his writings were not political, the silence about his creations seems peculiarly timid from the standpoint of contemporary literary profession. Equally disregarded was the illustrator Jože Beránek (1913-1945, officially declared dead in 1967) who illustrated most of Tomažič's prose work. He worked for the newspaper Slovenec since 1941 and he began his collaboration with Tomažič in 1942 as he illustrated his first book of short prose Pohorske pravljice (The Pohorje fairy tales). Beránek, still illustrating for Tomažič in 1944, he also drew for the propagandistic department of Home Guard which proved to be fatal for him. In the nineties the reprints of Tomažič's works, illustrated by Jože Beránek, were published in ten books (originally there were nine of them) by the Mohorjeva družba in Celje: Botra vila (Fairy Godmother), Čarovničina hči (The Witch's Daughter), Dravska roža (The Flower of Drava), Drvarka Marija (Woodcutter Maria), Mrtvo srce (The Dead Heart), Oglarjev sin (The Charcoal Burner's son), Pastirčkova nebesa (Swain's Heaven), Pohorske bajke (The Pohorje Tales), Pohorske legende (The Pohorje Legends), Pohorske pravljice (Pohorje Fairy Tales)
Keywords: Jože Tomažič’s prose; Jože Beránek’s illustration; Pohorje in literature